Contextualization: A Theology of Gospel and Culture, karya: Nicholls, Bruce J. - Martin Susanto (Sekolah Tinggi Teologi Satyabhakti, Malang)
Contextualization: A Theology of Gospel and Culture, karya: Nicholls, Bruce J.